Single incision surgical approach for the release of lacertus syndrome and cubital tunnel syndrome - Mohammed Muneer (3047970) (2025)
Background understanding the concept of multiple compression neuropathy syndrome has recently evolved, leading to better clinical assessment and evaluation. However, decompression of the involved nerves might require multiple incisions. Concomitant compression neuropathy, such as Lacertus Syndrome (LS) and cubital tunnel syndrome, is not uncommon. The traditional approach for releasing both nerves encompasses two separate surgical incisions. Minimazing surgical incisions is essential for postoperative scar management and nerve gliding. In this paper we describe a single surgical incision for releasing both compressions. Surgical technique To release the Lacertus Fibrosis using the classical surgical incision for cubital tunnel syndrome, an incision is made between the medial epicondyle and olecranon. After reaching the brachial fascia, the skin and subcutaneous tissue are raised as a one flap off the fascia. The lacertus fibrosis, identified as a thick rectangular or trapezoid stracture attached to the brachial fascia, is then incised to expose the median nerve beneath it. Conclusion As we advance towards the concept of multiple compression neuropathy, it is crucial to minimize surgical incisions to reduce pain, wound breakdown, scar formation, traction neuropathy, neuroma formation, and unsatisfactory aesthetic outcomes. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-025-06494-4